Biomolecular Regulation of Zinc Deposition to Achieve Ultra‐Long Life and High‐Rate Zn Metal Anodes. Issue 29 (24th June 2022) - Zhu, Jinlin; Deng, Wenjun; Yang, Na; Xu, Xianqi; Huang, Chao; Zhou, Yi; Zhang, Man; Yuan, Xinran; Hu, Jun; Li, Chang; Li, Rui
Abstract: Aqueous zinc‐ion batteries (ZIBs) have been extensively studied due to their inherent safety and high energy density for large‐scale energy storage. However, the practical application is significantly limited by the growing Zn dendrites on metallic Zn anode during cycling. Herein, an environmental biomolecular electrolyte additive, fibroin (FI), is proposed to guide the homogeneous Zn deposition and stabilize Zn anode. This work demonstrates that the FI molecules with abundant electron‐rich groups (NH, OH, and CO) can anchor on Zn anode surface to provide more nucleation sites and suppress the side reactions, and the strong interaction with water molecules can simultaneously regulate the Zn 2+ coordination environment facilitating the uniform deposition of Zn. As a consequence, only 0.5 wt% FI additive enables a highly reversible Zn plating/stripping over 4000 h at 1 mA cm −2, indicating a sufficient advance in performance over state‐of‐the‐art Zn anodes. Furthermore, when applied to a full battery (NaVO/Zn), the cell exhibits excellent capacity retention of 98.4% after 1000 cycles as well as high Coulombic efficiency of 99%, whereas the cell only operates for 68 cycles without FI additive. This work offers a non‐toxic, low‐cost, effective additive strategy to solve dendrites problems and achieve long‐life and high‐performance rechargeable aqueous ZIBs. Abstract : The long chain of fibroin (FI) molecules with abundant electron‐rich groups (CO, NH, and OH) can not only anchor the Zn surface but also regulate the solvation structure of zinc ions. Such an interfacial and electrolytic synergy effectively guides the uniform Zn plating/stripping to achieve an ultra‐long life over 4000 h.